Efficacy of Intraoperative Hypertonic Glucose Solution Administration on Persistent Air Leak After Extended Pleurectomy/Decortication for Malignant Pleural Mesothelioma: A Retrospective Case–Control Study - Testori, Alberto; Perroni, Gianluca; Alloisio, Marco; Voulaz, Emanuele; Giudici, Veronica Maria; Cariboni, Umberto; Bottoni, Edoardo (Frontiers in Oncology, 2021)
Background: Persistent air leak is a common complication occurring from 6 to 23% of cases after extended pleurectomy/decortication for malignant pleural mesothelioma. Treatment options for this complication after major lung resection are well documented in literature, nevertheless evidences in extended pleurectomy/decortication for malignant pleural mesothelioma are absent. Aim of the study is to evaluate the efficacy of intraoperative administration of 50 % hypertonic glucose solution in reducing duration of air leak following extended pleurectomy/decortication for malignant pleural mesothelioma. Materials and Methods: In this retrospective, case control study we analyzed our electronic health record and selected those patients with a histological diagnosis of malignant pleural mesothelioma who underwent extended pleurectomy/decortication in the period 2013-2021. From 2018, we introduced a lavage with 500 ml glucose solution at 50% concentration into the chest cavity at the end of surgical procedure. Patients operated before 2018 were used as control group. Postoperative glycemia was measured, patients were followed after hospital discharge until the air leak resolved and chest tube was removed. Statistical analysis was performed using R software. Results: a total of 71 patients met our criterion. Treatment and control groups where similar for age, sex, smoking status, number of comorbidities, tumor histotype and side of disease. Use of hypertonic glucose solution resulted in shorter chest tube maintenance after hospital discharge (p=0.0028). A statistically significant difference (p=0.02) was also found in postoperative glycemia between treatment (103 g/dL ± 8.9) and control group (98.8 g/dL ± 8.6). Days of hospitalization and chest tube maintenance during hospitalization did not significantly differed between the groups. Interpretation: Intraoperative administration of 50% hypertonic glucose solution reduced the duration of air leak after hospital discharge. An increase in postoperative glycemia was found in treatment group, although with no clinical effect. Hypertonic glucose solution is an effective and safe method to manage persistent air leak after extended pleurectomy/decortication for malignant pleural mesothelioma.